Business diplomacy influence on multinational corporations’ foreign economic activity processes - V. I. Ivanova; I. S. Presnova (Вестник университета, 2024)
Doing business internationally means facing a complex international business environment. The article presents a comprehensive analysis of business diplomacy in transnational corporations as a mechanism for managing complex interactions with governmental and non-governmental organizations. The purpose of the study is to develop basic recommendations for business diplomacy integration in the domestic companies’ activities based on the definition of its role in transnational corporations. The methodological basis of the study was formed by the papers of Russian and foreign scientists. The main functions that are in the area of business diplomacy responsibility have been defined. The main advantages for transnational corporations provided by business diplomacy, the importance of which is more realized in a weak institutional context, have been highlighted. Based on the parameters described by H. Ruël, T. Wolters, and R. Loohuis in “Business Diplomacy in Multinational Corporations”, the activity of Merz, which operates mainly in aesthetic medicine, has been analyzed from the point of implementing the principles and means of business diplomacy. Recommendations have been provided for multinational corporations to integrate the business diplomacy principles into their activities in order to increase its effectiveness. The authors concluded that business diplomacy strengthens a company’s position in the market, helps to expand its influence, and contributes to its development.